2018
DOI: 10.1021/acs.langmuir.7b03126
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Dependent Dissolution and Cellular Uptake of Silver Nanoparticles

Abstract: The cellular uptake and dissolution of trigonal silver nanoprisms (edge length 42 ± 15 nm, thickness 8 ± 1 nm) and mostly spherical silver nanoparticles (diameter 70 ± 25 nm) in human mesenchymal stem cells (hMSC's) and human keratinocytes (HaCaT cells) were investigated. Both particles are stabilized by polyvinylpyrrolidone (PVP), with the prisms additionally stabilized by citrate. The nanoprisms dissolved slightly in pure water but strongly in isotonic saline or at pH 4, corresponding to the lowest limit for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 90 publications
2
32
0
Order By: Relevance
“…Thus, cancerous cells typically have a lower stiffness (they are also defined as 'soft') when compared to the tumor tissue that they form and to normal cell lines, property which allows them to migrate and eventually metastasize [74,75]. The reported bending stiffness is 100 kPa for HaCaT cells [76], and varies from 0.76 kPa [77] to 3.9 kPa [78] for A375 cells depending on the experimental setup [79,80]. Considering those stiffness values, the stronger cytotoxicity that we observed on A375 compared to HaCaT could be explained by the high capacity According to ISO 10993-5, cell viability results can be interpreted as following: >80% no cytotoxicity, 80-60% weak cytotoxicity, 60-40% moderate cytotoxicity, and <40% strong cytotoxicity [60].…”
Section: Mtt Assaymentioning
confidence: 99%
“…Thus, cancerous cells typically have a lower stiffness (they are also defined as 'soft') when compared to the tumor tissue that they form and to normal cell lines, property which allows them to migrate and eventually metastasize [74,75]. The reported bending stiffness is 100 kPa for HaCaT cells [76], and varies from 0.76 kPa [77] to 3.9 kPa [78] for A375 cells depending on the experimental setup [79,80]. Considering those stiffness values, the stronger cytotoxicity that we observed on A375 compared to HaCaT could be explained by the high capacity According to ISO 10993-5, cell viability results can be interpreted as following: >80% no cytotoxicity, 80-60% weak cytotoxicity, 60-40% moderate cytotoxicity, and <40% strong cytotoxicity [60].…”
Section: Mtt Assaymentioning
confidence: 99%
“…Besides, the cellular compartment contained a lower AgNPs percentage (of the total Ag content) compared to the AgNPs percentage in the exposure concentration in the apical compartment. This suggests a preference towards cellular uptake/association of ionic silver over AgNPs or possible dissolution of the AgNPs cellularly following their uptake [44][45][46].…”
Section: The Interaction Of Ag and Agnps With Bewo B30 Placental Cellsmentioning
confidence: 99%
“…[19] The shape of the nanomaterial also plays a role in dissolution, cellular uptake, and reactivity. [20,21] For example, nanocubes of silver have been shown to be less toxic to the roots of the plant Lolium multiflorum than nanowires or quasi-spherical nanosilver particles. [21] In an in vivo daphnid study Nassar et al (2016) found that gold nanorods were more toxic and caused more generation of ROS than did nanospheres.…”
Section: All Nanomaterials Are Not Created Equal: Known Characteristimentioning
confidence: 99%